Poly(vinyl chloride) powder as a low-cost flame retardant modifier for epoxy composites. Issue 5 (4th July 2019) - Barczewski, Mateusz; Matykiewicz, Danuta; Sałasińska, Kamila; Kozicki, Damian; Piasecki, Adam; Skórczewska, Katarzyna; Lewandowski, Krzysztof
Abstract: For the purpose of the study, epoxy (EP) composites modified with 5–40 wt% of poly(vinyl chloride) (PVC) powder were manufactured. The influence of PVC powder on the fire behavior of EP-based composites was determined with a UL-94 HB test and cone calorimetry, supplemented by a thermogravimetric analysis. The fire behavior study showed that PVC powder may effectively decrease the flammability of EP in case of at least 20 wt% filler content while composites containing lower amounts of PVC powder (5 and 10 wt%) were characterized with significant improvement in tensile strength without reduction in flammability in reference to the unmodified EP.